2004
DOI: 10.1111/j.1365-2249.2004.02580.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tobacco smoke on interleukin-16 protein in human airways, lymphoid tissue and T lymphocytes

Abstract: SUMMARY CD4+ and CD8 + lymphocytes are mobilized in severe chronic obstructive pulmonary disease (COPD) and the CD8 + cytokine interleukin (IL)-16 is believed to be important in regulating the recruitment and activity of CD4 + lymphocytes. In the current study, we examined whether tobacco smoke exerts an impact not only on IL-16 in the lower airways but also in CD4 + or CD8 + lymphocytes or in lymphoid tissue. The concentration of IL-16 protein was measured by enzyme-linked immunosorbent assay (ELISA) in conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
25
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 21 publications
(23 reference statements)
5
25
0
Order By: Relevance
“…Many of these effects of smoking may result from the ability of nicotine to suppress immune system function [18,19]. Thus, nicotine has been reported to increase IL-16 levels, which may influence systemic immunomodulation by altering the number and responsiveness of systemic T lymphocytes in humans [20,21]. Nicotine has also been reported to differentially effect mouse splenocyte proliferation, with production of Th1 versus Th2 cytokines [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Many of these effects of smoking may result from the ability of nicotine to suppress immune system function [18,19]. Thus, nicotine has been reported to increase IL-16 levels, which may influence systemic immunomodulation by altering the number and responsiveness of systemic T lymphocytes in humans [20,21]. Nicotine has also been reported to differentially effect mouse splenocyte proliferation, with production of Th1 versus Th2 cytokines [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Two small studies of chronic bronchitis and COPD suggest a possible relationship between IL-16 and COPD. In a study of 33 smokers, BALF IL-16 was reported to be elevated with chronic bronchitis (Andersson et al, 2004) and in a study of 152 COPD patients and 80 controls, plasma IL-16 was lower in males with COPD, but there was no adjustment for potential confounding factors other than gender (de Torres et al, 2011). This study did not investigate emphysema and we are unaware of any studies investigating differences of IL16 mRNA in peripheral blood gene expression.…”
Section: Introductionmentioning
confidence: 89%
“…Previous researchers showed more CD8 + and CD4 + T cells in the lungs of patients with COPD, chronic bronchitis and even asymptomatic smokers compared with non‐smoking controls [4–15]. Comparing smokers with and without COPD, Saetta et al.…”
Section: Discussionmentioning
confidence: 99%
“…Lung inflammation is present in all smokers and is comprised of neutrophils, macrophages and T lymphocytes [4–6, 8, 9]. Concerning specific inflammation, CD4 + helper and especially CD8 + cytotoxic T lymphocytes have been shown to be increased in airways and lung parenchyma in COPD patients [4–16]. The excessive recruitment of T cells in the lung could be a consequence of a response to neoantigens induced by cigarette smoke in the case of ‘autoantigenic hypothesis of COPD’ or simply a response to viral infections (active or latent) that are common in this disease [9, 17, 18].…”
Section: Introductionmentioning
confidence: 99%